The Influence of Managerial Ownership, DOL, and DFL On Profitability - Arivatu Ni'mati Rahmatika; Siti Sofiana (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research aims to determine the effect of managerial ownership, DOL and DFL on profitability in tobacco subsector companies listed on the Indonesia Stock Exchange from 2018 to 2022. This type of correlational research employs methods of multiple linear regression analysis, panel data, namely random testing influence, hausman test, normality test, multicollinearity test, t test, F test, and coefficient of determination test with a significance of 0.05. Data processing uses eviews 10 application software. The samples of this research is taken from companies listed on the Indonesia Stock Exchange. Specifically Tobacco subsector. The research findings show that operating leverage has a partial influence on profitability, managerial ownership and financial leverage have no influence on profitability. Profitability is influenced simultaneously by managerial ownership, operating leverage, and financial leverage.